2017
DOI: 10.1002/fsn3.572
|View full text |Cite
|
Sign up to set email alerts
|

Development of omega‐3‐rich Camelina sativa seed oil emulsions

Abstract: Camelina sativa seed is an underutilized oil source rich in omega‐3 fatty acids; however, camelina oil is not fully explored for food applications. Its high omega‐3 content makes it susceptible to oxidation, which may limit food applications. Therefore, the main objective of this study was to investigate the potential of camelina seed oil to form physically and oxidatively stable emulsions as a potential delivery system for omega‐3 fatty acids. Effects of homogenization conditions, namely, pressure (15 MPa‐30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The collection of information was based on obtaining published scientific articles on the nutraceutical composition of Camelina sativa in regions of Europe, Asia and North America. With this survey, it was possible to obtain information on crops in Spain 2013 (Ciubota-Rosie, Ruiz, Ramón, & Pérez, 2013), New Jersey-US 2009 (Moser & Vaughn, 2010), Wilmington-US 2015 (Belayneh., Wehling., Cahoon., & Ciftci., 2015;Belayneh, Wehling, Zhang, & Ciftci, 2017), Minnessota-US 2016 (Walia et al, 2018), Poznán-Poland 2018 (Krzyżaniak et al, 2019), Turin-IT 2006(Pierreti et al, 2007, Romania (Toncea, Ghilvacs, & Prisecaru, 2013) In each environment, the average of all nutraceutical characteristics of Camelina sativa and meteorological variables was calculated. Then, the mean and standard deviation of each nutraceutical variable for all environments were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…The collection of information was based on obtaining published scientific articles on the nutraceutical composition of Camelina sativa in regions of Europe, Asia and North America. With this survey, it was possible to obtain information on crops in Spain 2013 (Ciubota-Rosie, Ruiz, Ramón, & Pérez, 2013), New Jersey-US 2009 (Moser & Vaughn, 2010), Wilmington-US 2015 (Belayneh., Wehling., Cahoon., & Ciftci., 2015;Belayneh, Wehling, Zhang, & Ciftci, 2017), Minnessota-US 2016 (Walia et al, 2018), Poznán-Poland 2018 (Krzyżaniak et al, 2019), Turin-IT 2006(Pierreti et al, 2007, Romania (Toncea, Ghilvacs, & Prisecaru, 2013) In each environment, the average of all nutraceutical characteristics of Camelina sativa and meteorological variables was calculated. Then, the mean and standard deviation of each nutraceutical variable for all environments were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Ratusz et al, quantified the amount of tocopherol in CSO using high performance liquid chromatography (HPLC) techniques and concluded that it contains 55-76 mg/100 g of tocopherol [15]. Belayneh et al estimated in their study that Camelina contains 760 mg/kg of tocopherol in the oil [16]. Present study was also aimed to analyze and quantify the tocopherol content present in CSO grown in Indian climatic conditions using a novel HPTLC technique.…”
Section: Introductionmentioning
confidence: 91%
“…For example, in a study by Chew et al [19], in the coating material, consisting of gum Arabic and sodium caseinate, β-cyclodextrin was added to fill the voids between these materials and reduced the access of oxygen in the oil encapsulated. In studies by Belayneh et al [6], control test of camelina oil began to show changes in oxidation at day 16, while emulsions made with wheat protein isolate only on day 28, which is explained by the surrounding of oil drops by the protein isolate. This indicates the need to protect the oil from oxidation.…”
Section: Peroxidase Valuementioning
confidence: 98%